Exploring the material culture of medical artifacts in the Oblate Collection - Jaworski, Sarah (Scientia Canadensis, 2024)
How can we explore object biographies when a collection has relied heavily on the donor’s narrative? This article uses three artifacts to explore the history of Ingenium’s Oblate Collection, a group of 282 medical artifacts used at L’Hôpital de L’Assomption in Grand Falls, New Brunswick, on the land of the Wolastoqiyik people. The hospital was opened in 1952 by the newly founded Secular Institute, a branch of the Oblate Missionaries of Mary Immaculate who ran 48 residential schools across Canada. Ingenium’s catalogue information relies largely on the narrative from the donors themselves, primarily two documents written by Oblate nurse Fabienne Rinfret, who describes life working in the hospital and how the artifacts were used by the staff. Our files lack stories of patient experiences or a fuller, more inclusive sense of their local context including connections to Indigenous people and land. To tell a fuller story of this collection, and f ill out missing historical dimensions, we can look to the artifacts themselves, and through a material-culture lens, discover new ways of knowing these objects.